2021
DOI: 10.36416/1806-3756/e20210054
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of tuberculosis: a consensus statement from the Brazilian Thoracic Association

Abstract: Early, accurate diagnosis of tuberculosis is one of the major pillars of the control of the disease. The purpose of this consensus statement is to provide health professionals with the most current, useful evidence for the diagnosis of tuberculosis in Brazil. To that end, the Tuberculosis Committee of the Brazilian Thoracic Association brought together 14 members of the Association with recognized expertise in tuberculosis in Brazil to compose the statement. A nonsystematic review of the following topics was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
0
13
0
8
Order By: Relevance
“…Firstly, it was observed that most patients started the treatment based on clinical symptoms and radiological diagnosis. This conduct is in accordance with the recommendations of the Brazilian Thoracic Association, given the context of limited resources, and the benefits of early diagnosis for treatment efficiency and the reduction of the transmission [18,23,24]. Chest radiography is a method of significant importance as it is easy to perform, accessible, inexpensive, and safe (using a low dose of radiation).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Firstly, it was observed that most patients started the treatment based on clinical symptoms and radiological diagnosis. This conduct is in accordance with the recommendations of the Brazilian Thoracic Association, given the context of limited resources, and the benefits of early diagnosis for treatment efficiency and the reduction of the transmission [18,23,24]. Chest radiography is a method of significant importance as it is easy to perform, accessible, inexpensive, and safe (using a low dose of radiation).…”
Section: Discussionmentioning
confidence: 54%
“…It should be requested for all patients with clinical suspicion of pulmonary TB [25]. Despite its low specificity, chest radiography is extremely valuable for physical examination, as it can detect multiple clinical changes and exclude associated lung disease [18]. On the other hand, chest computed tomography (CT) is more sensitive and specific than radiography in detecting early clinical changes, being able to distinguish active lesions from residual lesions in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Para otimizar os resultados, são recomendadas duas a três amostras de escarro, com pelo menos uma coleta no início da manhã e um volume ideal de 5-10 mL. A microscopia de fluorescência e centrifugação/sedimentação do escarro pode aumentar a sensibilidade da baciloscopia (SILVA et al, 2021).…”
Section: Diagnóstico Da Tb Pulmonarunclassified